Perbedaan Persepsi Kebahagiaan dan Kesadaran Diri pada Individu Jelang Dewasa Ditinjau dari Jenis Kelamin - Byosvelma Michelle Blessya Tucunan; Raynata Danielle Mulya; Yohana Intan Simbolon; Victoria Elizabeth Zefanya Runtu; Bonar Hutapea (Innovative: Journal Of Social Science Research, 2025)
Emerging adulthood, is a pivotal phase where genders, women and men influences experiences in profound ways. It is a period of brain maturation, learning about intimacy and mutual support, intensification of pre-existing friendships, family-oriented socialization, and the quality of life. Happiness and self-awareness are important goals on this journey, because these two factors contribute greatly to a person's quality of life. However, there are differences in thinking regarding perceptions between the two variables in individuals approaching adulthood. In this research, we want to review the existence of differences in perceptions between happiness and self-awareness through gender using non-experimental quantitative methods and probability sampling. Data were collected through distributing questionnaires to men and women aged 18-21 years. We implement the Awareness Outcomes Measure and the Oxford Happiness Questionnaire which were analyzed using MANOVA. F value for genders factor (0.081) is not significant (p = 0.9242 > 0.05). So these results shows indicate a moderate positive relationship between perception of self-awareness and happiness in emerging adulthood.